Women as primary teachers - Putnam, Abbie E. (My University, 1902)
Introduction: The various positions that are open to woman makes it a difficult problem for her to choose that place for which she is most fitted. Tho she is certain to succeed in any work which she may take up, yet it must be admitted that there are certain places for her in which she can achieve far greater success, and in which she is needed more than others, one of the most important of these places being that of primary teaching. This position was at first occupied only by man but as primary schools increased in number and efficiency, and woman, being allowed to enter this line of work, showed her superior ability to man, she has been gradually given a preference and today holds almost entire control of this department of education. Any why has woman been so successful in this line of work? Because, while by the law of the state the position is open to both sex by the law of nature it is exclusive to woman, woman being the natural educator of the child, born with a heart, love, sympathy and patience to produce that which is best and highest in the child.
Citation: Putnam, Abbie B. Women as primary teachers. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Women; Primary Teachers; Education; Theses; Manuscripts (documents)